2003
DOI: 10.1104/pp.102.019760
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Bacterial Recruitment of Plant Genes Associated with the Biosynthesis of Secondary Metabolites

Abstract: Microorganisms and plants synthesize an immense variety of metabolites, which are generally classified into two major groups based on their function. Primary metabolites are essential for growth and universally used, whereas secondary metabolism is highly diverse and variable and plays a role for the survival of the producing organism within its natural habitat (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 56 publications
1
31
0
7
Order By: Relevance
“…A reciprocal horizontal exchange of genetic information between the plant material and microorganisms seems to have been occurring continuously and the possibility that the pathways of phytohormone biosynthesis in green plants are of prokaryotic origin cannot be ruled out. As pointed out by Bode and Müller (2003), in contrast to the generally accepted hypothesis, several plant-specific metabolic pathways have in recent years also been found in prokaryotes. For instance cellulase synthase in vascular plants has been suggested to been transferred from cyanobacteria to plants (Nobles et al, 2001).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 88%
See 1 more Smart Citation
“…A reciprocal horizontal exchange of genetic information between the plant material and microorganisms seems to have been occurring continuously and the possibility that the pathways of phytohormone biosynthesis in green plants are of prokaryotic origin cannot be ruled out. As pointed out by Bode and Müller (2003), in contrast to the generally accepted hypothesis, several plant-specific metabolic pathways have in recent years also been found in prokaryotes. For instance cellulase synthase in vascular plants has been suggested to been transferred from cyanobacteria to plants (Nobles et al, 2001).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 88%
“…Several observations indicate that a reciprocal horizontal exchange of genes has been occurring between the plant material and microorganisms and therefore microbial origin of phytohormone synthesis genes cannot be ruled out (Johri, 2004). First of all, many microorganisms grow in close association with plant material and this would enhance chances of DNA uptake (Bode and Müller, 2003). While discussing the origin of land plants, Pirozynski and Mallloch (1975) concluded "land plants never had an independence (from fungi); for if they had they could never have colonized land" (italics intentional by Johri for emphasis).…”
Section: Were the Pathways For The Biosynthesis Of Phytohormones In Gmentioning
confidence: 99%
“…The key biosynthetic gene is phlD, which displays interesting similarity to genes for plant chalcone synthases. This type III polyketide synthase is unusual in prokaryotes, and it was suggested that the gene may have been acquired by horizontal gene transfer (5,6,12). In contrast, phylogenetic analysis of phlD does not support this theory, so the provenance of 2,4-DAPG production remains uncertain (52,53).…”
mentioning
confidence: 89%
“…Gene sce1440, encoding a terpene cyclase, has substantial similarity to genes in other bacteria that are involved in biosynthesis of geosmin 29,30 , a sesquiterpene-derived natural product that gives soil its characteristic smell. The genome also encodes an unusual L-dopa decarboxylase 31 and two type III PKSs; a gene encoding one of the PKSs, sce2133, shows similarity to bacterial RppA-encoding genes (61% identity) 32 . Although the compound has not yet been isolated from S. cellulosum So ce56, expression of sce2133 in Pseudomonas putida resulted in biosynthesis of flaviolin 33 , supporting the utility of heterologous hosts for identifying the products of cryptic myxobacterial clusters and dissecting gene function.…”
Section: Secondary Metabolism and Biotechnological Potentialmentioning
confidence: 99%